Recent Strategies to Overexpress and Engineer Cellulases for Biomass Degradation - Datta, Supratim (Current Metabolomics, 2016)
Bioenergy is one of the best options towards replacing fossil fuels with renewable, carbon-neutral alternatives. To generate bioenergy at an industrial scale, we must be able to design an optimized cell factory that will convert chemically complex residual biomass or lignocellulose to useful liquid fuels. Microorganisms have evolved a sophisticated enzymatic machinery to degrade these heterogeneous biomass substrates to soluble sugar. These enzyme cocktails are primarily composed of various glycoside hydrolases (GHs) and act synergistically to efficiently cleave the glycosidic linkages in the biomass. Here we review the current strategies to engineer and improve cellulases and the efforts to understand and create microbes with improved catalytic proficiencies.
Keywords: lignocellulose